Bilateral Adrenal Incidentalomas: A Case Report and Review of Diagnostic Challenges. (9th January 2013) - Carlson, Anders L.; Marney, Annis M.; Anderson, Scott R.; Gilbert, Matthew P.
Abstract : Incidentally discovered adrenal masses (incidentalomas) are common and present challenges both in diagnosis and management. When incidentally discovered adrenal masses are bilateral, a refined diagnostic approach is warranted since bilateral disease is more likely to be pathologic. We review a case of a 34-year-old man with incidentally discovered bilateral adrenal nodules. A comprehensive diagnostic strategy led to the diagnosis of bilateral pheochromocytoma caused by von Hippel-Lindau syndrome. He was successfully treated with bilateral laparoscopic adrenalectomy and has recovered well. While the initial diagnostic approach is similar to the unilateral incidentaloma, additional testing and/or genetic testing should be considered in the case of the bilateral adrenal mass.